Community resilience and community development: What mutual opportunities arise from interactions between the two concepts?. Issue 2 (15th March 2019) - Cavaye, Jim; Ross, Helen
ABSTRACT: While overtures have been made in both directions, few have observed a mutual opportunity for resilience to be a goal in community development, or community development to be a key method in fostering community resilience. This article reviews the extent of mutual acknowledgement between these fields, and argues what each field can learn from the other, especially in terms of the practice of community development and enabling resilience. Community development—and some of its components such as capacity building, empowerment, and building networks—offers a key approach to building community resilience. Resilience thinking suggests that community development practitioners can expand their practice to help communities deal with dynamically changing systems. They can emphasize building adaptive capacity, managing complexity, enhancing community values and identity, managing multiple level systems, and supporting community agency. We offer advice and identify watchpoints for a co-evolving practice.